High-resolution CT findings of pulmonary infections after orthotopic liver transplantation in 453 patients - Qin, J (The British Institute of Radiology., 2012)
OBJECTIVES: The objective of this study was to review the high-resolution CT (HRCT) findings in patients with pulmonary infection after orthotopic liver transplantation (OLT) and to determine distinguishing findings among the various types of infection. METHODS: This study included 453 consecutive liver transplant recipients with pulmonary infection, on whom HRCT of the chest was performed within 24 h of the beginning of symptoms and for whom proven diagnosis had taken place within 1 week of the onset of symptoms. Two radiologists analysed the CT images; final decisions regarding the findings were reached by consensus. RESULTS: Bacterial and viral pneumonia made up the bulk of infections (63.4% and 29.4%, respectively), followed by fungal infiltrates (24.5%). Large nodules were most common in patients with fungal pneumonia, having been seen in 38 (54%) of the 70 patients with fungal pneumonia, 22 (10%) of 220 with bacterial pneumonia (p=0.0059) and 6 (8%) of 78 with viral pneumonia (p=0.0011). The halo sign was also more frequent in patients with fungal pneumonia, having been seen in 38 (54%) of the 70 patients with fungal pneumonia, 17 (8%) of 220 with bacterial pneumonia (p=0.0026) and 7 (9%) of 78 with viral pneumonia (p=0.0015). There was no statistically significant difference in the prevalence of the other HRCT patterns including air-space consolidation, ground-glass attenuation and small nodules among bacterial, viral and fungal infections (all p>0.05). CONCLUSION: The presence of large nodules with the halo sign is most suggestive of fungal infection after OLT. Other HRCT patterns are not helpful in distinguishing among the various types of infection seen in liver transplant recipients.